Gene therapy targeting inflammatory pericytes corrects angiopathy during diabetic wound healing - Jin, Wenxv; Chen, Xiong; Kong, Lingguo; Huang, Chongqing (Frontiers in Immunology, 2022)
Wound healing is impaired in the diabetic status, largely attributable to the diabetes-associated angiopathy. Pericytes play critical roles in the stabilization of the formed vessels. The loss and dysfunction of pericytes have been reported in inflammation during diabetes and associated with the pathology of diabetic angiopathy. However, a practical approach that targets inflammatory pericytes to improve the diabetic wound healing is lacking. In the current study, we showed that the inflammatory pericytes from wound skin of diabetic patients were impaired in growth potential and underwent oxidative stress and apoptosis. Expression of antioxidant gene oxidation resistance protein 1 (OXR1) specifically in pericytes through an adenovirus carrying OXR1 under a pericyte-specific neuron glia antigen-2 (NG2) promoter (AV-NG2p-OXR1) relieved the oxidative stress, reduced the apoptosis and recovered the growth potential in diabetic pericytes. Moreover, expression of OXR1 in diabetic pericytes retrieved their potential of both suppressing the migration of co-cultured HUVECs and inducing cell aggregates at the branching points, indicating a functional recovery. In vivo gene therapy using this AV-NG2p-OXR1 to DB/DB mice, the mouse model for type 2 diabetes, significantly improved wound healing, likely through enhancing blood flow at the wound rather than increasing vessel density. Together, our data suggest that¬ gene therapy targeting inflammatory pericytes may improve diabetes-associated impaired wound healing.